What is better/reliable, mitosis counting or Ki67/MIB1 staining? - Kriegsmann, Mark; Warth, Arne (Translational Lung Cancer Research, 2016)
Uncontrolled proliferation is a hallmark of cancers and tumor cell division is a prerequisite for the effectiveness of most conventional anticancer treatments. Thus, by either counting mitotic figures (mitotic index; MI) or immunohistochemical analysis of proliferation associated antigens like Ki-67 (proliferation index; PI), proliferation in cancers was assessed in a multitude of scientific studies. PubMed research for the terms “cancer” AND “proliferation” as well as “lung cancer” AND “proliferation” results in >190,000 and >16,000 hits, respectively. However, despite this exhausting amount of literature the translation of proliferation assessment into daily routine has largely failed. It has its role in some grading systems, e.g., Elston-Ellis grading for breast cancer or the French Federation of Cancer Centers Sarcoma Group (FNCLCC) grading for sarcomas, but has currently no diagnostic meaning for thoracic tumors despite for neuroendocrine tumors, where MI is used to separate typical from atypical carcinoids or large cell neuroendocrine carcinomas. Why was this promising biomarker lost in translation?
Gesehen am 29.05.2020